Molecular imaging probes for 31P contrast - Tear, L (2018)
31P magnetic resonance has yet to realise its clinical potential principally due to the relatively low sensitivity of the 31P nucleus. While 31P-MRS can uniquely provide vital information regarding in vivo phosphorus metabolism, the long acquisition times required are incompatible with observing dynamic changes in phosphorus speciation (e.g. monitoring ATP/phosphocreatine ratios in real time). This thesis reports how heptadentate Gd.DO3A derivatives can be used to enhance 31P relaxivity reducing T1 values by more than an order of magnitude per millimolar Gd. This enables shorter repetition times markedly improving the signal to noise ratio (SNR) per unit time. These complexes bind in fast exchange with phosphate species, while linear commercial Gd complexes were found to demonstrate competitive binding of ATP to Gd. Structural modifications of the DO3A complex were found to alter the affinity for specific phosphate species, as monitored by luminescence spectroscopy of the europium complexes, and also influenced the relaxivity of the Gd complex. In vivo, the phosphate species of interest reside intracellularly and therefore cellular uptake of these complexes was investigated, using fluorescence microscopy on luminescent complexes and NMR diffusion methods for the gadolinium complexes themselves. The complexes were found to remain extracellular or display endosomal uptake. These results indicate that these systems have clear potential as extracellular 31P contrast agents. Alternative approaches will be required to achieve intracellular 31P contrast.